Institutional Repositories in the Indonesian Higher Education Sector: Current State and Future Prospect - Liauw, Toong Tjiek (Curtin University, 2018)
This research aims to provide the first detailed survey of various aspects of institutional repositories serving Indonesia’s higher education sector. This includes establishing the current state of implementation of repositories and their major characteristics, and assessing their future potential. The study adopts a mixed-methods research strategy. Methods employed are: 1) a longitudinal content analysis of university repository websites; 2) an online survey of Indonesian academics; and 3) interviews with stakeholders in three Indonesian universities.